2015
DOI: 10.1007/s00107-015-0932-y
|View full text |Cite
|
Sign up to set email alerts
|

On the semi-rigidity of dovetail joint for the joinery of LVL panels

Abstract: This paper focuses on multiple tab-and-slot joints (MTSJ) for load-carrying assembly of structural wood elements, which are inspired by traditional cabinetmaking joints and adapted for automatic fabrication and engineered wood panels such as laminated veneer lumber. First a numerical method is presented for the estimation of the connections' semi-rigid properties based on box beam samples. In a simplified model, the mechanical behavior of the joint is represented by potential elastic slips at interfaces. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Roche et al (2015a) showed that the shear strength of finger-and dovetail-jointed plywood plates is similar to the shear strength of screwed connections. Li et al showed that the connectors can be combined with metal fasteners, and further research by Roche et al (2015b) compared the rotational stiffness of joints at ridges, demonstrating the particular strength of through-tenon joints.…”
Section: Robotic Assemblymentioning
confidence: 94%
“…Roche et al (2015a) showed that the shear strength of finger-and dovetail-jointed plywood plates is similar to the shear strength of screwed connections. Li et al showed that the connectors can be combined with metal fasteners, and further research by Roche et al (2015b) compared the rotational stiffness of joints at ridges, demonstrating the particular strength of through-tenon joints.…”
Section: Robotic Assemblymentioning
confidence: 94%
“…The development of these 2D FE models was expanded for grooving timber interfaces by Girardon et al [44,45]. Roche et al [46] studied the semi-rigidity of the dovetail joint for a beam on two supports with a numerical model developed with MATLAB R (The MathWorks Inc., Natick, USA).…”
Section: Numerical Modelsmentioning
confidence: 99%
“…This simplified the handling, transport, and final assembly of the shell. The mechanical strength of the joints, which has been examined separately by Roche and colleagues, [8][9][10] was studied without the use of adhesives. Figure 25(a) shows the NURBS target surface of the prototype.…”
Section: × 16 Segment Shell Prototypementioning
confidence: 99%